Frontiers in Deep-Sea Equipment and Technology - Cui, Weicheng; Lian, Lian; Pan, Guang (Journal of marine science and engineering, 2023)
The conflict between population, resources, and environment in the twenty-first century made the ocean the strategic space and resource treasure of human society to realize sustainable development [...]